Crisi e innovazione istituzionale. Le riforme dei governi locali in Italia e Spagna - Bolgherini, Silvia (SocietàMutamentoPolitica, 2015)
The outbreak of the global crisis in 2007-2008 marked a critical juncture both internationally and domestically for most western countries. Economic crises often have an impact on institutional structures and in fact the current crisis prompted national governments to introduce reforms. Italy and Spain have both been dramatically affected by the global crisis, although with different intensity, features and reactions. Both countries introduces territorial reforms due to deeply modify the institutional structure of the relevant local government. In this contribution it will be argued that territorial reforms were already on the national agendas and the global crisis accelerated their (re)start; that Italy and Spain chose different path for reform although starting from the same exogenous context and having the same final aim; finally, that some crucial aspects concerning inter-institutional relations, which should have been addressed by the reforms, risk to remain unattended also after the reforms.